Efektifitas Pemberantasan Tindak Pidana Perjudian Online Melalui Situs Pusatkoin di Wilayah Hukum Direktorat Reserse Kriminal Khusus Polda DIY: Penelitian - Hernanda Pramana Adji; HM. Zaki Sierrad; Elza Qorina Pangestika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The phenomenon that occurs in society of gambling crimes, including online gambling, is a serious problem in Indonesia that is difficult to eradicate, even though it has become a criminal act. Gambling, especially online gambling, continues to grow along with the advancement of information technology, and its impacts cover various aspects, including economic, psychological, and social. Empirical legal research consists of research on legal identification and research on legal effectiveness. "Empirical research must also see and review the values that live in society with applicable laws and regulations.The discussion has been explained at length in the previous chapters in this paper, so the conclusion is obtained . The effectiveness of eradicating online gambling crimes, especially through the "pusatkoin" site in the jurisdiction of the DIY Regional Police, requires a comprehensive approach. The DIY Regional Police needs to strengthen law enforcement efforts, increase cooperation with related parties, and optimize prevention through public education and blocking gambling sites . Eradicating online gambling crimes, especially through the "pusatkoin" site, requires integrated and sustainable efforts. The DIY